Trainings in the activities of the Kharkiv regional center for social services in wartime - Huseynov, Andriy; Yevdokymova, Iryna (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2024)
War in Ukraine has caused large-scale social challenges that require prompt solutions and adaptation measures from both governmental and non-governmental organizations, including social service centers. The Kharkiv Regional Social Service Center plays a key role in ensuring social protection for vulnerable groups, providing methodological support, and enhancing the professional competence of social service professionals.The aim of this article is to define the specifics and the problems of the training activities of the Kharkiv Regional Social Service Center under wartime conditions.The article proposes a definition of training as an organized learning process that involves the use of special methods and approaches to provide participants with the necessary skills and knowledge. It also presents classifications of training and characterizes the main stages of their organization and implementation.The author notes that training has become an essential area of work for regional social service centers in Ukraine since 2020, including the Kharkiv Regional Social Service Center. The article analyzes the specifics of the center’s activities under wartime conditions and presents the results of empirical research conducted through surveys of training participants and a trainer from the Kharkiv Regional Social Service Center. The survey results indicate that most participants positively evaluate the center's training activities, highlighting their practical focus, topicality, and high level of organization. At the same time, certain challenges were identified, including security concerns, logistical constraints, and the need to expand training topics.The article also provides recommendations for improving the training activities at the Kharkiv Regional Social Service Center. In particular, it emphasizes the importance of flexible training formats, including a combination of offline and online events, expanding the range of training topics, and improving their methodological foundation.